(untitled) (Educação e Pesquisa, 2022)
This article discusses the pedagogical documentation and the aesthetic principles established in the guidelines of early childhood education. It aims to review to what extent the documenting path contributes to expanding sensitivity, the production of meanings and the possibilities of living together in early childhood education. The research, conducted in a qualitative perspective, stems from the following question: Does the documenting gesture make teachers aware of meeting and be together in early childhood education? The study carried out within the scope of a master’s degree in education had as sample a group of ten teachers who worked in early childhood education and who participated in a formative experience carried out in an extension course woven along the course of documenting. The survey instruments included participants’ observation, written, photographic and audiovisual records, documentation and, above all, being together with the teachers. From the dialogue between the normative guidelines and different authors, the aesthetic principle in the gesture of documenting is highlighted, because the encounter with the sensitive allows the expansion of borders, the possibility of affectation and the search for meanings and senses in the relationships woven between children and adults in everyday education. The training experience with teachers, built through the path of documenting, makes it possible to question assumptions naturalized in pedagogical practice, making important shifts in the ways of being and staying together in early childhood education.